Enhancing adolescents’ healthy behaviors through nutrition and reproductive health education to prevent stunting at SMP N 1 Gedangsari, Gunungkidul - Urrahman, Dhiya; Baiquni, Fahmi; Hersipa, Lulung Lanova; Rahmawati, Nur Cahya; Karuniawati, Benny (Community Empowerment, 2025)
Many adolescents pay insufficient attention to their nutritional needs, which increases their risk of developing anemia and chronic energy deficiency (CED). These conditions can elevate the likelihood of giving birth to stunted children in the future. In Yogyakarta, the prevalence of stunting is 18%, with Gunungkidul having the highest rate at 22.2%. Furthermore, Gunungkidul recorded 58 cases of adolescent childbirth, highlighting the urgent need for intervention. This community service activity aimed to enhance adolescents’ awareness and knowledge of reproductive health and nutrition to prevent stunting from an early age. The activity was conducted at SMP N 1 Gedangsari and employed a participatory approach with an educational method. The educational program successfully increased the adolescents’ awareness and knowledge of reproductive health and nutrition as crucial factors in stunting prevention. The interactive and participatory nature of the educational approach showed positive impacts, and it is expected that similar programs can be continued to provide long-term benefits to the community.